Visual evoked potentials waveform analysis to measure intracortical damage in a preclinical model of multiple sclerosis - Marenna, Silvia; Rossi, Elena; Huang, Su-Chun; Castoldi, Valerio; Comi, Giancarlo; Leocani, Letizia (Frontiers in Cellular Neuroscience, 2023)
Introduction: Visual evoked potentials (VEPs) are a non-invasive technique routinely used in clinical and preclinical practice. Discussion about the inclusion of VEPs in McDonald criteria, used for Multiple Sclerosis (MS) diagnosis, increased the importance of VEP in MS preclinical models. While N1 is peak interpretation is known, less is known about the first and second positive VEP peaks, P1 and P2, and the temporal dispersion of the different segments. Our hypothesis is that, P2 latency delay describes intracortical neurophysiological dysfunction from the visual cortex to the other cortical areas. Methods: Analyzed VEP traces included in our recent two published papers. Compared with these previous published papers other latencies VEP peak, P1 and P2, and latencies dispersion, of the components P1-N1, N1-P2 and P1-P2, were analyzed in blind. Results: Latencies of P2, P1-P2, P1-N1 and N1-P2 were increased in all EAE mice, including the group without N1 latency change delay at early time points. In particular, at 7 dpi the P2 latency delay change was significantly higher compared with N1 latency change delay. Moreover, new analysis of these VEP components under the influence of stimulation revealed a decrease in the delay in stimulated animals. Discussion: P2 latency delay change, P1-P2 dispersion, P1-N1, and N1-P2 latency changes which reflect intracortical dysfunction, were consistently detected across all EAE groups before the N1 change. Results underline the necessity to analyze all VEP components for a complete overview of the neurophysiological visual pathway dysfunction and treatment efficacy.